Marine Biodiversity Patterns and Processes, Assessment, Threats, Management and Conservation - Queiroga, H.; Cunha, M.R.; Cunha, A.; Moreira, M.H.; Quintino, V.; Rodrigues, A.M.; Serôdio, J.; Warwick, R.M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
This volume presents selected contributions given to the 38th European Marine Biology Symposium, held in Aveiro, Portugal, in September 2003. Understanding the functioning of Marine Ecosystems is the first step to measure and predict the influence of Man, and to find solutions for the enormous array of problems we face today. This volume is organised according to the four subthemes of the symposium and to issues commonly perceived as relevant by scientists concerned with the study, protection and management of Marine Biodiversity: patterns and processes, assessment, threats and management and conservation. The 32 papers that make up this book represent the current research and concerns about Marine Biodiversity in Europe, and will have wide appeal to all those interested in understanding and preserving the marine ecosystems of the world's oceans. Reprinted from HYDROBIOLOGIA volume 555(2006).
Patterns And Processes -- The relationship between phytoplankton diversity and community function in a coastal lagoon -- Ascendency as ecological indicator for environmental quality assessment at the ecosystem level: a case study -- Phytoplankton seasonality in a highly stratified karstic estuary (Krka, Adriatic Sea) -- Factors controlling phytoplankton blooms in a temperate estuary: nutrient limitation and physical forcing -- The near-bottom layer as an ecological boundary in marine ecosystems: diversity, taxonomic composition and community definitions -- Seasonal and spatial patterns of distribution of subtidal benthic invertebrate communities in the Mondego River, Portugal — a poikilohaline estuary -- Benthic ecology of semi-natural coastal lagoons, in the Ria Formosa (Southern Portugal), exposed to different water renewal regimes -- Inter-annual variability of soft bottom macrofaunal communities in two Ionian Sea lagoons -- Spatial patterns of benthic macroinvertebrates in intertidal areas of a Southern European estuary: the Tagus, Portugal -- Structure and dynamics of a benthic invertebrate community in an intertidal area of the tagus estuary, western portugal: a six year data series -- Spatial and environmental factors affecting the distribution of the main decapod crustacean prey species in the NW Mediterranean -- Probing diversity in the plankton: using patterns in Tintinnids (planktonic marine ciliates) to identify mechanisms -- Fish assemblages in different shallow water habitats of the Venice Lagoon -- The effect of zostera noltii, spartina maritima and scirpus maritimus on sediment pore-water profiles in a temperate intertidal estuary -- Biogeographic patterns of intertidal macroinvertebrates and their association with macroalgae distribution along the Portuguese coast -- Seasonal variations of cystoseira barbata (stackhouse) C. Agardh frond architecture -- Epifaunal inventory of two shipwrecks from the Belgian Continental Shelf -- Assesment -- Using asymmetrical designs for environmental impact assessment of unplanned disturbances -- Threats -- Mass mortality of coral reef ascidians following the 1997/1998 El NiñO event -- Changes in the range of some common rocky shore species In Britain — A Response To Climate Change? -- Effects of dredging activities on population dynamics of Posidonia oceanica (L.) Delile in the Mediterranean sea: the case study of Capo Feto (SW Sicily, Italy) -- The colonisation of human-made structures by the invasive alga Codium fragile ssp. tomentosoides in the north Adriatic Sea (Ne Mediterranean) -- Immediate effects of experimental human trampling on mid-upper intertidal benthic invertebrates at the Asinara Island MPA (NW Mediterranean) -- Imposex in Hexaplex trunculus at some sites on the North Mediterranean Coast as a base-line for future evaluation of the effectiveness of the total ban on organotin based antifouling paints -- Environmental effects of marine fish pond culture in the Ria Formosa (Southern Portugal) -- Time-series evolution of toxic organisms and related environmental factors in a brackish ecosystem of the Mediterranean Sea -- Management and Conservation -- Assessing the sensitivity of seabed species and biotopes — the Marine Life Information Network (MarLIN) -- Characterisation of the European Marine Sites in South West England: the Fal and Helford candidate Special Area of Conservation (cSAC) -- Macrobenthic colonisation of artificial reefs on the southern coast of Portugal (Ancão, Algarve) -- The benthic impacts of the Loch Linnhe Artificial Reef.
Keywords: Nature conservation; Biodiversity; Aquatic ecology .; Nature Conservation; Biodiversity; Freshwater & Marine Ecology